STUDY OF THE EFFECT OF MACROECONOMIC INDICATORS ON MUDHARABAH SAVINGS IN INDONESIAN SHARIA BANKING - Abidin, Ali Zainal (Hunafa: Jurnal Studia Islamika, 2023)
This study will discuss the impact of the profit level shares, interest rates BI, inflation, and the number of Islamic banking offices on the mudharabah savings in Indonesia. The population are the whole unit of Sharia banking in Indonesia, while the research sample was selected from 60 pieces divided into five variables. Each variable represents 12 samples selected based on monthly data. Research data were obtained from secondary sources like Bank Indonesia, Financial Services Authority, Sharia Commercial Banks, and Sharia Business Units with data period from January 2017 – December 2021. Time series data includes monthly statistical reports on BI interest rate data, inflation, and monthly banking reports in Sharia. The data analysis method uses the Eviews application with linear regression analysis. The results indicate that the variables for profit-sharing, BI rate, inflation, and several offices simultaneously have a significant effect on mudharabah savings in Islamic banks in Indonesia.